SafetyNet: streamlining and automating QA in radiotherapy. (8th January 2016) - Hadley, Scott W.; Kessler, Marc L.; Litzenberg, Dale W.; Lee, Choonik; Irrer, Jim; Chen, Xiaoping; Acosta, Eduardo; Weyburne, Grant; Keranen, Wayne; Lam, Kwok; Covington, Elizabeth; Younge, Kelly C.; et al.
Abstract : Proper quality assurance (QA) of the radiotherapy process can be time‐consuming and expensive. Many QA efforts, such as data export and import, are inefficient when done by humans. Additionally, humans can be unreliable, lose attention, and fail to complete critical steps that are required for smooth operations. In our group we have sought to break down the QA tasks into separate steps and to automate those steps that are better done by software running autonomously or at the instigation of a human. A team of medical physicists and software engineers worked together to identify opportunities to streamline and automate QA. Development efforts follow a formal cycle of writing software requirements, developing software, testing and commissioning. The clinical release process is separated into clinical evaluation testing, training, and finally clinical release. We have improved six processes related to QA and safety. Steps that were previously performed by humans have been automated or streamlined to increase first‐time quality, reduce time spent by humans doing low‐level tasks, and expedite QA tests. Much of the gains were had by automating data transfer, implementing computer‐based checking and automation of systems with an event‐driven framework. These coordinated efforts by software engineers and clinical physicists have resulted in speed improvements in expediting patient‐sensitive QA tests. PACS number(s): 87.55.Ne, 87.55.Qr, 87.55.tg, 87.55.tm